Narasi Eksploitasi Perempuan Dalam Film Perempuan-Perempuan Liar - Fadhilah, Ummi, Fajar Junaedi, M.Si (2017)
Women as an icon, can be an attraction for the audience to watch what is showed by media. Unfortunately, new culture that is coming makes meaning of "woman as an icon" changed into women utilization, in an exploitation format in the media. This research has aims for knowing how exploitation of women happens in a narrative of film. Using Tzvetan Todorov narrative's analysis model, can be known globally and clearly how exploitation of women happens in a narrative of film. There are five structure of narrativethis research can know easily the meaning of a narrative in every stages. In this research, will use actant model and square opposition from Algirdas Greimas that has structure, those structure can help to simplify in understanding every characters that have relation between a character to each other, using opposition model too, this can describe many various of viewpoint and condition of people in watching exploitation of women in the narrative of film. Result of this research will show that using Tzvetan Todorov model, it can be known how women exploitation in the narrative of film Perempuan-Perempuan Liar, and how various of exploitation happens in every stages. On the other hand, using actant model and square opposition, exploitation can not always be watched in every stages, but it can be known how viewpoint of people about women exploitation in the narrative. Keywords: narrative analysis, exploitation films, woman